Highly dispersed Ni/Al2O3 catalysts for dry reforming of methane prepared by alkaline-induced adsorption process. (22nd August 2022) - Liu, Xupeng; Zhang, Lei; Zheng, Xiangqian; Zhang, Yimin; He, Dedong; Luo, Yongming
Abstract: Ni–Al catalysts were widely developed for methane dry reforming (DRM) and other valuable reactions, but the low utilization of Ni species on the Al2 O3 support has limited its further application. In this paper, Ni species were induced to anchor on the mesoporous Al2 O3 under alkaline conditions. Notably, alkaline treatment caused the corrosion and restructure of the mesoporous Al2 O3, and this reorganization process of Al2 O3 and the presence of defects from ligand-unsaturated Al 3+ (Alpenta 3+ ) promoted Ni species to remain uniform dispersion on the surface. In combination with TEM, HRTEM, UV–vis and H2 chemisorption, it is observed that Al2 O3 formed a special layered stacking structure under alkaline conditions, which contributed to the homogeneous distribution of Ni species on the catalyst surface. Surprisingly, the catalyst showed good low-temperature DRM reactivity, which was superior to the conventional Ni–Al catalysts prepared by impregnation method and the most Ni–Al catalysts reported in the literatures. The CH4 reforming rate of RCH4-mNi  = 80.16 (L/h/g) at 550 °C was obtained on the conventional impregnation catalyst, while the Ni–Al catalysts by adsorption showed a significant increase in the CH4 reforming rate of RCH4-mNi R CH 4 − mNi  = 160.87 (L/h/g). Consequently, the present work provides some ideas for the synthesis of efficient Ni–Al catalysts for DRM as well as other meaningful reactions. Graphical abstract: Image 1 Highlights: Alkaline treatment caused the restructure of the mesoporous Al2 O3 . Alkaline treatment Al2 O3 exhibited a lamellar morphology with cavity structures. The lamellar morphology of Al2 O3 promoted Ni remaining uniform dispersion. Ni/Al2 O3 from alkaline-induced adsorption showed higher reactivity for DRM.